Feedback Filtered-OFDM Waveform Candidature for Interference Mitigation in 5G Networks and Beyond - Augustine, Zakka; Yaro, Abdulmalik Shehu; Tekanyi, Abdoulie Momodou Sunkary; Bello, Habeeb; Abdu-Aguye, Umar-Faruk; Agbo, Ezekiel Ehime (International Journal of Integrated Engineering, 2025)
The ever-growing demand for more filtered waveforms to improve communication system’s quality triggered the development of a novel Feedback Filtered-Orthogonal Frequency Division Multiplexing (FF-OFDM) Channels Access (CA) technique. This work presented some significant applications of FF-OFDM, which are the capability of mitigating Inter-Channels Interference (ICI), Inter-Symbols Interference (ISI), and Adjacent Channels Interference (ACI) better than previous CA techniques. This research introduced a paradigm shift from the traditional method of mitigating ICI, ISI, and ACI to a more advanced method using Artificial Intelligence (A1) coded non-unity feedback probe. At 60 kHz Subcarrier Spacing (SCS), the FF-OFDM obtained an interference power mitigation of 47.0 dB for ICI, 39.0 dB for ISI, and 27.0 dB for ACI, outperforming the conventional model of Filtered Orthogonal Frequency Division Multiplexing (F-OFDM) which realized 31.6 dB for ICI, 27.0 dB for ISI, and 22.0 dB for ACI. For the tests of the performance of the communication channel, the FF-OFDM achieved a Bit Error rate (BER) within  at 27 dB Signal-to-Noise Ratio (SNR) better than realized by conventional and modified versions of F-OFDM.  Effective interference mitigation to improved signal quality is a requirement by Third Generation Partnership Project (3GPP) for the Fifth Generation (5G) New Radio (NR) objectives.